Epitaxial quantum dot lasers on silicon with high thermal stability and strong resistance to optical feedback - H. Huang; J. Duan; B. Dong; J. Norman; D. Jung; J. E. Bowers; F. Grillot (APL Photonics, 2020)
This work investigates the performance of 1.3-μm quantum dot lasers epitaxially grown on silicon under optical feedback sensitivity with different temperature and doping profiles. Experiments show that these quantum dot lasers exhibit a very high degree of resistance to both incoherent and coherent optical feedbacks. 10 Gbps penalty-free transmissions are also unveiled under external modulation and at different temperatures. The paper draws attention on quantum dot lasers with p-doping that exhibit a better thermal resistance, a lower linewidth enhancement factor, a higher critical feedback level, and a better spectral stability with less intensity noise. Together, these properties make epitaxial quantum dot lasers with p-doping more promising for isolator-free and Peltier-free applications, which are meaningful for future high-speed photonic integrated circuits.